Estimation of a Preference-Based Summary Score for the Patient-Reported Outcomes Measurement Information System: The PROMIS®-Preference (PROPr) Scoring System. (August 2018) - Dewitt, Barry; Feeny, David; Fischhoff, Baruch; Cella, David; Hays, Ron D.; Hess, Rachel; Pilkonis, Paul A.; Revicki, Dennis A.; Roberts, Mark S.; Tsevat, Joel; Yu, Lan; Hanmer, Janel
Background . Health-related quality of life (HRQL) preference-based scores are used to assess the health of populations and patients and for cost-effectiveness analyses. The National Institutes of Health Patient-Reported Outcomes Measurement Information System (PROMIS ® ) consists of patient-reported outcome measures developed using item response theory. PROMIS is in need of a direct preference-based scoring system for assigning values to health states.Objective . To produce societal preference-based scores for 7 PROMIS domains: Cognitive Function–Abilities, Depression, Fatigue, Pain Interference, Physical Function, Sleep Disturbance, and Ability to Participate in Social Roles and Activities.Setting . Online survey of a US nationally representative sample ( n = 983).Methods . Preferences for PROMIS health states were elicited with the standard gamble to obtain both single-attribute scoring functions for each of the 7 PROMIS domains and a multiplicative multiattribute utility (scoring) function.Results . The 7 single-attribute scoring functions were fit using isotonic regression with linear interpolation. The multiplicative multiattribute summary function estimates utilities for PROMIS multiattribute health states on a scale where 0 is the utility of being dead and 1 the utility of "full health." The lowest possible score is –0.022 (for a state viewed as worse than dead), and the highest possible score is 1.Limitations . The online survey systematically excludes some subgroups, such as the visually impaired and illiterate.Conclusions . A generic societal preference-based scoring system is now available for all studies using these 7 PROMIS health domains.